Development of Socio Scientific Issues (SSI) Based E-Lkpd on Thermochemical Material as an Effort to Improve Students' Science Literacy and Enviromental Care Skills - Zaki Dayatul Akbar; Jimmi Copriady; Rasmiwetti (Universitas Tidar, 2025)
This study aims to develop E-LKPD based on Socio Scientific Issue (SSI) on Thermochemistry material as an effort to improve students' science literacy skills and environmental care. The background of this research is based on the low science literacy of students, the lack of use of innovative teaching materials that link science with social issues, and the low concern of students for the environment. The method used is development research (Research and Development) with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. E-LKPD products were developed using Canva and Flip PDF Corporation 2025 applications, and validated by material experts and media experts. The validation results showed that the E-LKPD was in a very valid category, with a validity percentage of 91.22% by material experts and 92.22% by media experts. Small-scale trials were conducted in 3 schools, namely Cendana Pekanbaru High School, Alhuda Pekanbaru High School and Seri Rama Pekanbaru High School. The average percentage of teacher responses was 90.3 and the average percentage of student responses was 90.1. The large-scale trial was conducted at SMA Cendana Pekanbaru. The results of the trial showed that the E-LKPD was practical and effective in learning. The effectiveness of E-LKPD is seen from the significant increase in science literacy and environmental care of students, shown through t-test and the acquisition of N-Gain Score of 0.78 for science literacy and 0.81 for environmental care. Thus, the development of SSI-based E-LKPD is proven to be valid, practical, and effective in improving the science literacy skills and environmental care attitudes of students on Thermochemistry material. Keyword: E-LKPD, Socio Scientific Issue (SSI), Thermochemistry, Science Literacy, Environmental Care